PENGARUH MODEL INDUKTIF KATA BERGAMBAR TERHADAP KETERAMPILAN BERCERITA SISWA KELAS III SDN DI GUGUS IV LABUAPI TAHUN AJARAN 2018/2019 - Fitria Rahmawati; Ida Bagus Kade Gunayasa; Lalu Hamdian Affandi (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2020)
This study aims to determine the effect of picture word inductive model on storytelling skill of third grade SDN in Labuapi IV group academic year 2018/2019. This research is a quantitative study with quasi-experimental and nonequivalent control group design. The population is all of class III students in Labuapi IV group. The technique of collecting data using the storytelling skill test directly and observation. The conclusion obtained in this study is the picture word inductive model have high influential toward the storytelling skill of third grade students in SDN Labuapi in academic year 2018/2019.